Educational Innovation at Assuniyyah Al Jauhari Kencong Jember Islamic Boarding School - Ula, Muhammad Bahrul; Nurhidayati, Titin (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
The main aim of this research is to highlight two things related to educational innovation at the Assunniyyah Aljauhari Kencong Islamic Boarding School. The type of research is qualitative phenomenological using a phenomenological approach. Interview techniques with key informants were used as a data collection procedure. The findings of this research show that the innovations carried out at the Islamic boarding school include establishing a formal school, forming a special dormitory for tahfidzul Qur'an, and creating a special yellow book education. Supporting and inhibiting factors were found in the innovation process carried out. It was concluded that this was the basis for implementing educational innovation in the Islamic boarding school.